2003
DOI: 10.1016/s0016-7037(02)01345-5
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coupling between trace and major elements and a model for calculation of magma residence times using plagioclase

Abstract: Residence times of plagioclase crystals in magma reservoirs can be determined by modeling the compositional zoning of trace elements in these crystals. We present a formulation to model diffusion of trace elements in plagioclase paying special attention to certain thermodynamic and kinetic aspects. In particular, we account for the compositional dependence on anorthite content of the chemical potential and diffusion coefficients of trace elements (e.g., Mg), the choice of suitable boundary conditions and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
129
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(132 citation statements)
references
References 46 publications
3
129
0
Order By: Relevance
“…Plagioclase, for example, can show sharp step-function-like gradients in Li (Charlier et al 2012) and Mg (Costa et al 2003) between anorthite-and albite-rich regions in partially equilibrated samples. If the different chemical potentials of the trace elements between the two chemically distinct domains are not considered, then estimated D·t values from Li and Mg concentration gradients would be incorrect (Costa et al 2003). However, these observations contain key differences to those made here for our zircon work.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plagioclase, for example, can show sharp step-function-like gradients in Li (Charlier et al 2012) and Mg (Costa et al 2003) between anorthite-and albite-rich regions in partially equilibrated samples. If the different chemical potentials of the trace elements between the two chemically distinct domains are not considered, then estimated D·t values from Li and Mg concentration gradients would be incorrect (Costa et al 2003). However, these observations contain key differences to those made here for our zircon work.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…However, these observations contain key differences to those made here for our zircon work. First, these studies identified Mg and Li compositional gradients correlating with anorthite mol% variations from 40 to 80, and 40 to 50 %, respectively (Costa et al 2003;Charlier et al 2012). In our zircon data, however, the minor element cation substitutions of REE for Zr and P for Si make up ~1 % or less of the cation sites in zircon.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…Geospeedometers have the ability to extract cooling information of natural rocks from mineral compositions using analytical or numerical models (e.g., Dodson, 1973;Eiler et al, 1992;Ganguly and Tirone, 1999;Costa et al, 2003;Müller et al, 2013;Watson and Cherniak, 2015;Liang, 2017). Applying the closure temperature equation of Dodson (1973) to Ca in olivine, two research groups estimated cooling rates of oceanic gabbros from the Faak et al (2013) as a function of silica activity and (b) the differences of two existing silica activity models for a basaltic system.…”
Section: Introductionmentioning
confidence: 99%
“…Because Faak et al's thermometer was calibrated only at 1100-1200 • C for plagioclase with 50-80 mol% anorthite, it is unclear how accurately their thermometer can be extrapolated to lower temperatures (e.g., 700-900 • C; Faak et al, 2015), at which Mg in gabbros has been extensively reset by diffusion. Although the 1-D plane sheet diffusion model is easy to implement, it is likely inadequate for 3-D shaped crystals with substantial diffusive resetting (e.g., Ganguly and Tirone, 1999;Costa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Olivine is one of the most useful minerals for such studies (e.g., Gerlach and Grove 1982;Nakamura 1995;Martin et al 2008) because it commonly occurs in mafic magma, and its rapid Mg-Fe interdiffusion enables timescales to be estimated at less than 1 month. Recently, Mg in plagioclase has been used to provide time scales of days to years (e.g., Costa et al 2003Costa et al , 2008Druitt et al 2012;Ruprecht and Cooper 2012). Magnetite phenocrysts are particularly useful in silicic magma systems for detecting the processes within days to months before eruption (e.g., Nakamura 1996; Devine et al 2003;Chertkoff and Gardner 2004;Tomiya and Takahashi 2005) because of their rapid diffusion (Van Orman and Crispin 2010) and common occurrence in various types of magma.…”
Section: Introductionmentioning
confidence: 99%